Micromorphological Identification and Prevalence of Sarcocystis Species in Slaughtered Sheep: A Tri-Method Approach - Ankitha, Shetti; Udaya Kumar, Manchukonda; Dasmabai, Banothu; Kalyani, Putty (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A study was conducted to determine the prevalence of Ovine Sarcocystosis in sheep slaughtered at various slaughterhouses in and around Hyderabad, Telangana, India. A total of 1,000 muscle samples, comprising oesophagi and hearts were subjected to gross examination. Gross inspection revealed no macrocysts in any of the samples. For microscopic evaluation, 150 samples (90 hearts and 60 oesophagi) were analyzed using squash technique, pepsin-HCl muscle digestion. The squash technique revealed microsarcocysts in 5 out of 90 heart samples (5.5%), while none were detected in oesophageal samples resulting in an overall prevalence of 3.33%. In contrast, the pepsin HCl digestion technique demonstrated a significantly higher detection rate identifying bradyzoites in 49 heart samples (54.4%) and 18 oesophagi (30.0%) yielding an overall prevalence of 44.6%. Microscopic confirmation of bradyzoites was achieved through Giemsa and Leishman staining which revealed banana-shaped bradyzoites with posterior nuclei under oil immersion. Histopathological examination further confirmed the presence of microsarcocysts in cardiac muscles. This study highlights a high prevalence of microscopic Sarcocystosis in the cardiac muscles of slaughtered sheep in and around Hyderabad, emphasizing the superiority of the digestion technique over squash method and the potential zoonotic and economic implications of subclinical infections in livestock.